“A casa tornou-se minha mente": a representação da realidade em The House of Hunger, de Dambudzo Marechera - Andrade, Nayara Cristina Rodrigues de (2016)
The aim of this research and of the dissertation resulting from it is the analysis of the construction of the representation of reality in the book The House of Hunger (1978), by Dambudzo Marechera. Prominent writer from Zimbabwe, inscribed in the African Literature in English, his works do not have yet translations into Portuguese. In his own country, he has suffered several accusations for refusing to write according to the Preand Post-Independence national call to the production of works under the 19th century Realism and the 20th century Socialist Realism. His rejection of these “traditions” has resulted in a critical fortune that sometimes vilifies his works for being antirealist and anti-mimetic. This work focuses primarily on tracing how the concept of mimesis already presented differences in Ancient Greece, through Plato’s and Aristotle’s ideas, and how the contribution of the theorist Erich Auerbach (2013) collaborates for the analysis and understanding of the construction of the representation of reality in the works by Dambudzo Marechera, which re-evaluates the charges against the author afore mentioned. For the development of this thesis, we decided to focus our attention on the novel “The House of Hunger” and the short stories “Burning in the Rain” and “The Transformation of Harry”, through the analysis of how the choice of the narrative point of view used in the works and how their narratives are constructed help for the construction of the representation of reality. In the Third Chapter, we made use of the postcolonial theories by Homi Bhabha (1998) and Frantz Fanon (2005) to help us analyze how mimesis is built in the short story “Black Skin What Mask”, through an identity crisis suffered by the protagonist-character. The short-story, which has in its title an obvious paraphrase of the title of Fanon’s Black Skin, White Masks (2008), has the construction of reality emerging through the tension between the fictional entity and the environment, which is a configuration of what Erich Auerbach understands mimesis is.